Hyperviscosity Syndrome in Paraprotein Secreting Conditions Including Waldenstrom Macroglobulinemia - Weaver, Allison; Rubinstein, Samuel; Cornell, Robert F. (Frontiers in Oncology, 2020)
Hyperviscosity syndrome is a serious complication associated with high levels of paraproteins in patients with hematological malignancies. Therapeutic advances in disease control may reduce the incidence of hyperviscosity syndrome; however, management of acute cases requires an understanding of key symptoms and prompt treatment to mitigate serious consequences.